Sarcopenia and aspartic acid magnesium - Shigeru Yamada; Eriko Kizaki; Aya Ozeki; Mio Nakagawa; Hitomi Fujita (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Sarcopenia from aging, inactivity, weightlessness, disease and malnutrition causes social problems due to associated physical dysfunction, a decrease in QOL, and risk of death. As a means of alleviating sarcopenia, appropriate exercise and nutrition therapy is required. However, nourishment therapy is especially important for a person in a situation where exercise is not feasible for maintaining skeletal muscle mass and muscular strength. Therefore, the authors studied the inhibitory effect of aspartic acid magnesium on disuse muscle atrophy. Herein we have described two of the mechanisms of action of aspartic acid magnesium on disuse muscle atrophy suppression. Initially, inactivity causes a decrease in capillary and oxygen supply, inhibits ATP synthesis, and produces active oxygen. As a result, the proteolysis system is activated and muscle atrophy progresses. We have described the effect of aspartic acid magnesium uptake on this mechanism, and the imbalance of the intracellular mineral with the inactive proteolysis system. The above is the content of this review.